Respuesta :

Answer:

[ -3 +(-5)][-3-(-5)]

( -8)(2)

= 16

Step-by-step explanation:

where there's x put-3 and where there's y put-5

I don't see =0 so I don't believe you will have to equate further

Answer:

-16

Step-by-step explanation:

Hello There!

For this one we also need to plug in the values and solve

(-3+(-5)(-3-(-5)

first lets distribute the -3 to -3 and -(-5)

-3x-3=9

-3x5=-15

9-15=-6

now lets distribute the -5 to the -3 and -(-5)

-5x-3=15

-5x5=-25

-25+15=-10

-10-6=-16

so the answer would be -16

ACCESS MORE